2011
DOI: 10.1371/journal.pone.0024145
|View full text |Cite
|
Sign up to set email alerts
|

Haemolysis during Sample Preparation Alters microRNA Content of Plasma

Abstract: The presence of cell-free microRNAs (miRNAs) has been detected in a range of body fluids. The miRNA content of plasma/serum in particular has been proposed as a potential source of novel biomarkers for a number of diseases. Nevertheless, the quantification of miRNAs from plasma or serum is made difficult due to inefficient isolation and lack of consensus regarding the optimal reference miRNA. The effect of haemolysis on the quantification and normalisation of miRNAs in plasma has not been investigated in great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
487
3
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 462 publications
(518 citation statements)
references
References 52 publications
13
487
3
15
Order By: Relevance
“…One issue that we would like to reiterate is the potential of contaminating cellular material, which has a higher concentration of miRNAs than plasma or serum, to confound miRNA quantitation (Kroh et al 2010). This contamination could arise from the presence of intact blood cells in serum/plasma or lysis of these cells (hemolysis) during sampling and processing (Duttagupta et al 2011, Kirschner et al 2011, McDonald et al 2011. Recent work found that an additional centrifuge step after plasma preparation efficiently removes intact blood cells and a significant fraction of contaminating cellular miRNAs (Duttagupta et al 2011).…”
Section: Association Between Androgen Signaling and Circulating Mirnamentioning
confidence: 99%
See 3 more Smart Citations
“…One issue that we would like to reiterate is the potential of contaminating cellular material, which has a higher concentration of miRNAs than plasma or serum, to confound miRNA quantitation (Kroh et al 2010). This contamination could arise from the presence of intact blood cells in serum/plasma or lysis of these cells (hemolysis) during sampling and processing (Duttagupta et al 2011, Kirschner et al 2011, McDonald et al 2011. Recent work found that an additional centrifuge step after plasma preparation efficiently removes intact blood cells and a significant fraction of contaminating cellular miRNAs (Duttagupta et al 2011).…”
Section: Association Between Androgen Signaling and Circulating Mirnamentioning
confidence: 99%
“…Hemolysis, which frequently occurs at low levels during collection of serum/plasma, is a more difficult problem to circumvent. Two studies have highlighted the profound effect hemolysis can have on miRNA concentrations in blood fluids (Kirschner et al 2011, McDonald et al 2011. The extent of hemolysis can be estimated by the measurement of free hemoglobin and certain miRNAs (e.g.…”
Section: Association Between Androgen Signaling and Circulating Mirnamentioning
confidence: 99%
See 2 more Smart Citations
“…Hemolysis during sample preparation can alter the microRNA content of plasma or serum. 10 In addition, small differences in duration and centrifugal force can create differences in the presence of platelets in plasma, ranging from platelet rich to platelet poor or free plasma, which has an impact on the microRNA repertoire.…”
mentioning
confidence: 99%